Analisis Korelasi Dakwah Tauhid terhadap Kualitas Umat Dalam Kisah Ulul ‘Azmi - Adib Umam, Muhammad Uswah; Miftakhussurur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the correlation of the dakwah of monotheism to the quality of the people through the stories of the ulul ‘azmi in the Qur’an. The method used in this research is library research with a qualitative approach.The results of this study conclude that people who accept the call to monotheism have very good qualities of faith, intellectual or intelligence qualities, and moral and social qualities in their lives and become people who receive salvation from Allah. While people who reject and deny the call to monotheism have very weak qualities of faith, and poor moral qualities which lead them to the wrath of Allah. This study also concludes that there are six dakwah strategies for da’i that can be applied in order to achieve a people with good quality in life. Keywords: Al-Quran; Dakwah; Monotheism; People and Ulul ‘Azmi.